2017
DOI: 10.4236/psych.2017.86058
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between a Night Usage of Mobile Phone and Sleep Habit and the Circadian Typology of Japanese Students Aged 18 - 30 yrs

Abstract: This study tries to investigate the current relationship between the habit to use mobile phone and the diurnal type scale and sleep habit in Japanese students.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…For example, 98% of the students attending junior high school affiliated to Faculty of Education, Kochi University has their own smart-phone in 2016 (Tsunomori, Harada et al, unpublished). Kawada et al (2017) reported that university students who put their own smart-phones in their beds during night sleep were significantly much more evening-typed than those who put it far from their beds. Also in junior high school students, the shifting to more evening-typed life is very dangerous for them to grow in the adolescent days from physical (disturbed menstrual cycles for females adolescents: Takeuchi et al, 2005) and mental view points (higher frequency to be anger, irritated, out-of control of emotion and depressed: Harada et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…For example, 98% of the students attending junior high school affiliated to Faculty of Education, Kochi University has their own smart-phone in 2016 (Tsunomori, Harada et al, unpublished). Kawada et al (2017) reported that university students who put their own smart-phones in their beds during night sleep were significantly much more evening-typed than those who put it far from their beds. Also in junior high school students, the shifting to more evening-typed life is very dangerous for them to grow in the adolescent days from physical (disturbed menstrual cycles for females adolescents: Takeuchi et al, 2005) and mental view points (higher frequency to be anger, irritated, out-of control of emotion and depressed: Harada et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Bedtime smartphone use has been known to worsen sleep quality and consequent daytime function in adults, and was associated with depressed mood in adolescents (6, 7). Overuse of smartphones in bed was proven to be associated with poor sleep quality, mental health, and delayed chronotype in Japanese college students (8). There underlie several mechanisms for this phenomenon; firstly, the screen light emitted from smartphones significantly suppresses the secretion of melatonin, and consequently disrupts sleep (9).…”
Section: Introductionmentioning
confidence: 99%
“…The so-called 24-hour society, which is currently in progress in Japan, seems to change environmental conditions surrounding the children. For example, mobile phones are used by more than 90% in 2000 and more than 98% in 2017 of university students, and more than 30% in 2000 and 95% in 2017 of junior high school students living in the urban area of Kochi city (33°N) had their own mobile phone (currently, most ones have smart phones) [4,5]. Students can communicate with their colleagues even in the middle of the night with mobile phones.…”
Section: Introductionmentioning
confidence: 99%
“…Students can communicate with their colleagues even in the middle of the night with mobile phones. Frequent or long-time (more than 30 min) usage of the mobile phone makes university and junior high school students more evening-typed [4,5]. At least for Japanese students in junior and senior high schools and universities, convenience stores have critical items for usual life, and these provide many kinds of foods and other goods for usual life.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation